2021
DOI: 10.3389/fgene.2021.767348
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-Coding RNAs in Post-Transcriptional Regulation of Lung Diseases

Abstract: Non-coding RNAs (ncRNAs), notably microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), have recently gained increasing consideration because of their versatile role as key regulators of gene expression. They adopt diverse mechanisms to regulate transcription and translation, and thereby, the function of the protein, which is associated with several major biological processes. For example, proliferation, differentiation, apoptosis, and metabolic pathways demand fine-tuning for the precise development of a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 196 publications
(186 reference statements)
0
10
0
Order By: Relevance
“…miRNAs are small non-coding RNA sequences of ±22 nucleotides that regulate gene expression at post-transcriptional level by repressing translation of specific mRNA targets through complementary pairing with their 3' untranslated regions. Growing evidence points to their potential role in chronic inflammatory diseases impacting lung tissues, such as in CF (15)(16)(17)(18)(19)(20)(21). Indeed, studies have shown that CF patients have a dysregulation in the expression of number of miRNAs, including those targeting the mutated CFTR transporter or its derivatives, such as miR-145 or miR-494 (18,22), or those involved in inflammatory pathology, such as the miR-126, miR-17 or miR-155 (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small non-coding RNA sequences of ±22 nucleotides that regulate gene expression at post-transcriptional level by repressing translation of specific mRNA targets through complementary pairing with their 3' untranslated regions. Growing evidence points to their potential role in chronic inflammatory diseases impacting lung tissues, such as in CF (15)(16)(17)(18)(19)(20)(21). Indeed, studies have shown that CF patients have a dysregulation in the expression of number of miRNAs, including those targeting the mutated CFTR transporter or its derivatives, such as miR-145 or miR-494 (18,22), or those involved in inflammatory pathology, such as the miR-126, miR-17 or miR-155 (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding ribonucleic acids (lncRNAs) are greater than 200 nucleotides, have no protein coding functions, and are widely involved in biological processes (13,14). Most lncRNAs have been implicated in the occurrence and development of COPD (15,16). LncRNA nuclear enriched abundant transcript 1 (NEAT1) is thought to be involved in a variety of cancers and inflammatory diseases (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has suggested that noncoding RNAs (ncRNAs) play important roles in a variety of inflammatory diseases, particularly allergic asthma. 12 Importantly, ncRNAs, including long noncoding RNAs (lncRNAs) with sizes larger than 200 nucleotides, microRNAs (miRNAs), and circular RNAs (circRNAs), among others, are being recognized as important molecules regulating coding genes at the transcriptional or posttranscriptional level in individuals with allergic asthma. 13 Multiple studies have emphasized that the effects of miRNAs on the initiation and maintenance of asthma are mainly achieved by regulating the expression of mRNAs at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%